Bioelectrical Impedance Analysis for Monitoring Fluid and Body Cell Mass Changes in Patients Undergoing Cardiopulmonary Bypass - Mustafa Göz; Cemil Sert; Abdussamet Hazar; Mehmet Salih Aydın; Nazim Kankılıç (Brazilian Journal of Cardiovascular Surgery, 2020)
Abstract Objective: To evaluate preoperative and postoperative body fluid distribution with a bioelectrical impedance analyzer in patients undergoing cardiopulmonary bypass. Methods: Fifteen adult patients undergoing cardiopulmonary bypass were included in this study. Total body fluid changes, basal metabolism rates, body fat masses, lean body masses, and total cell masses were recorded. The patients’ values were measured before anesthesia, after anesthesia, after sternotomy, at the 5th, 30th, and 60th minutes of cardiopulmonary bypass, and on the 1st, 3rd, and 5th postoperative days. All values were compared with preoperative values. Results: Total body fluid changed significantly after cardiopulmonary bypass (P<0.01). Metabolic velocity significantly changed compared to preoperative measurements (P<0.05). Fat mass and lean body mass also changed significantly. Body mass index and phase angle did not change significantly (P>0.05). Conclusion: Changes in body fluids during and after cardiopulmonary bypass are inevitable. The increase in total body weight shows that this fluid load shifts to the extracellular space during bypass and the fluid load in this area passes into the intravascular area in the early postoperative period. This may cause edema and dysfunction in the major organs. Therefore, the fluid balance should be adjusted very carefully, especially during the bypass phase and the early postoperative period.